Comprehensive analysis of molecular characteristic and clinical prognosis of CD8+ T cell related genes in idiopathic pulmonary fibrosis - Lin Feng; Jiabo Yuan; Xiaobing Dou; Yanlin Liu (PLoS ONE, 2025)
Idiopathic pulmonary fibrosis (IPF) is a progressive, life-threatening interstitial lung disease whose pathogenesis remains unclear. There is evidence showing the possible role of CD8+ T cells in the pathogenesis of IPF and the correlation with the clinical symptoms of IPF. In order to further explore the role of CD8+ T cells in IPF, we screened CD8+ T cell related genes (CRG) that are associated with IPF prognosis, and established the molecular typing characteristics of IPF. Subsequently, CXCR4, GPR56 and PAK1 were screened as independent prognostic factors. Expression profiles and multivariate analysis coefficients were used to establish and validate prognostic features of IPF. Immuno-infiltration characteristics of the established feature were also analyzed. Subsequent in vitro experiments verified the abnormal expressions of three independent prognostic factors in TGF-β1 treated IPF model at protein and mRNA levels. Our findings shed new light on the important role of CD8+ T cells in the pathogenesis of IPF and provide potential targets for predicting prognosis and possible future clinical applications.